2011
DOI: 10.1590/s1677-55382011000200008
|View full text |Cite
|
Sign up to set email alerts
|

Focal therapy with high-intensity focused ultrasound for prostate cancer in the elderly: a feasibility study with 10 years follow-up

Abstract: Purpose: To evaluate the long-term efficacy of prostate cancer control and complication rates, in the elderly, after focal therapy with high-intensity focused ultrasound (HIFU). Materials and Methods: Between June 1997 and March 2000, patients with localized prostate cancer were included into a focal therapy protocol. Inclusion criteria were: PSA ≤ 10 ng/mL, ≤ 3 positive biopsies with only 1 lobe involved, clinical stage ≤ T2a, Gleason score ≤ 7 (3+4), negative CT scan and bone scan. Hemi-ablation of the prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(44 citation statements)
references
References 37 publications
1
41
0
2
Order By: Relevance
“…There are few published data on follow-up FT series for PCa. Despite good functional results and percentages of residual tumour in the treated areas being between 0 and 23% [14,15,16,17], there are sparse descriptions of the pathological findings in the untreated areas. When this data is described, the presence of PCa in the contralateral lobe detected in follow-up PB ranges from 10 to 13.7% [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…There are few published data on follow-up FT series for PCa. Despite good functional results and percentages of residual tumour in the treated areas being between 0 and 23% [14,15,16,17], there are sparse descriptions of the pathological findings in the untreated areas. When this data is described, the presence of PCa in the contralateral lobe detected in follow-up PB ranges from 10 to 13.7% [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…No evident injury has been observed around or above the tissues penetrated by ultrasound. 20,21 High-intensity focused ultrasound also elicits other biological effects, such as proapoptosis and an improved cellular immune response, 22 in addition to the direct eradication by thermal effects. Clinical studies have indicated that HIFU has been extensively recognized as a local treatment not only to control local tumors but also to relieve pain and improve the quality of life of patients without severe side effects.…”
Section: Discussionmentioning
confidence: 99%
“…The authors report urinary tract infections in two patients and acute urinary retention in one, but a stabilization of international prostate symptom scores at 1 year and overall cancer-specific survival of 100%. 50 Another group reported early cancer control with a cohort of 20 patients treated with hemiablation. The trifecta of continence, erections, and cancer control was achieved in 89% of patients.…”
Section: Dovepressmentioning
confidence: 99%